PENERAPAN PENDEKATAN SAINTIFIK BERSTRUKTUR REALISTIC MATHEMATICS EDUCATION UNTUK MENGEMBANGKAN KEMAMPUAN PROBLEM SOLVING MATEMATIS SISWA - Samaray, Silvana; Sugiatno, Sugiatno; Hartoyo, Agung (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research intends to explain and analyze the result of the application of RME structured scientific approach to develop student’s mathematical problem solving  abilities in junior high school. The research is conducted using Pedagogical Action Research in two cycles. The result shows (1) Student’s mathematical problem solving  abilities were weak before RME structured scientific approach implemented to the teaching, the percentage ability was 20,56%, average pre-test score was 20,81 and 0% for study completeness; (2) The use of RME structured scientific approach in teaching students was implemented accordingly to the plan that had been set, its six steps of the approach ran optimally; 3) Student’s mathematical problem solving  abilities increased significantly after the teaching, percentage average of mathematical problem solving increased to 79,08%, average test score increased to 82,72 and study completeness increased to 74,07%; (4) Implementation result of RME structured scientific approach can develop student’s mathematical problem solving  ability. It is proved by the average percentage of mathematical problem solving ability achievement increased by 58,53%, test score increased by 61,91 score and study completeness percentage inceased by 74,07 %.  Keywords: Scientific Approach, RME Approach, Mathematical Problem Solving Ability.